Statistical optimization and analyses of the method of forming radar images in the time and frequency domains - Zhyla, S.S.; Odokiienko, O.V.; Kovaljchuk, D.I.; Shcherbyna, K.O.; Sydorov, Y.D. (Radiotekhnika, 2025)
The article presents a statistically grounded approach to the formation of scatterometric radar images based on stochastic signal processing. The developed mathematical model takes into account the spatial structure of the reflecting surface, as well as the physical and statistical characteristics of radar signals. The proposed optimal algorithm combines detection, Fourier transformation, decorrelation filtering, and estimation of surface reflectivity coefficients. It is shown that such an approach ensures high resolution and increased noise immunity of the radar system. The statistical optimization is carried out according to the maximum likelihood criterion with minimization of mean square error, using the Cramér–Rao lower bound. The analysis covers both time and frequency domains, with an emphasis on practical implementation of whitening filters and decorrelation procedures in real signal conditions. Simulation examples confirm the theoretical efficiency of the algorithm and justify its application in airborne radar systems using linear frequency modulated signals for high-precision imaging.